A comparative study on sample preparation procedures for supplementary foods by ICP-OES: Green chemistry considerations. Issue 8 (20th March 2015) - Ruiz-de-Cenzano, Manuela; Rochina-Marco, Arancha; Ruiz, Jessica; Cervera, M. Luisa; de la Guardia, Miguel
Abstract : An inductively coupled plasma optical emission (ICP-OES) method was developed for the simultaneous determination of major, minor and trace elements in food. Abstract : An inductively coupled plasma optical emission (ICP-OES) method was developed for the simultaneous determination of major, minor and trace elements in food. Preliminary studies focused on selecting suitable operational conditions in order to provide the highest sensitivity and to maximize the number of analytes to be determined without spectral or matrix interference. Ruthenium and rhenium were evaluated as internal standards and samples were analyzed at different dilution levels. Furthermore, a comparative study was carried out by using three sample digestion methods, microwave-assisted digestion with HNO3 /H2 O2, dry ashing and dry ashing with Mg(NO3 )2 /MgO as an ashing aid. Adequate precision and accuracy were assured by the analysis of spiked samples and certified reference material NIST 1573a tomato leaves. The method was successfully applied to the analysis of supplementary foods.